2022
DOI: 10.3389/fpls.2022.943740
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptomic and metabolomic profiling reveals the differences between alfalfa sprouts germinated with or without light exposure

Abstract: Alfalfa sprouts are among the most nutritionally rich foods, and light exposure is a critical factor in determining their biomass and quality. However, detailed metabolic and molecular differences between yellow and green alfalfa sprouts remain unclear. In this study, comprehensive metabolomic and transcriptomic analyses were integrated to evaluate the nutrient composition of alfalfa sprouts during germination with or without light exposure. Differentially expressed genes and differentially accumulated metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Research has further elucidated the potential health-promoting effects of alfalfa sprouts. Studies have demonstrated the cholesterol-lowering properties of alfalfa sprouts, attributed to their high fiber content and saponin compounds, as well as anti-diabetic and anti-obesity properties [ 17 , 18 , 19 , 20 ]. Also, alfalfa sprouts contain phytoestrogens, such as coumestrol, which may have protective effects against hormone-related cancers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has further elucidated the potential health-promoting effects of alfalfa sprouts. Studies have demonstrated the cholesterol-lowering properties of alfalfa sprouts, attributed to their high fiber content and saponin compounds, as well as anti-diabetic and anti-obesity properties [ 17 , 18 , 19 , 20 ]. Also, alfalfa sprouts contain phytoestrogens, such as coumestrol, which may have protective effects against hormone-related cancers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiutak et al showed that RGB-light-treated alfalfa sprouts were more effective and had higher β-carotene, lutein, and polyphenol contents than cool white light and warm white light [24]. The findings of Zhang et al illustrated that more isoquercitrin was produced in soybean sprouts under dark conditions, while more isoflavones were produced in mung bean sprouts after light exposure [25]. The effects of red and blue light, as well as mixed red and blue light, on the nutritional quality and antioxidant activity of alfalfa sprouts have been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…This bioprocess also enhances vitamin and bioactive compound levels. Common seeds used for sprouts include alfalfa (Logan et al, 2001 ; Zhang et al, 2022 ), broccoli (Chiriac et al, 2020 ; Subedi et al, 2019 ), clover (Dębski et al, 2021 ; Zhang et al, 2022 ), radishes (Subedi et al, 2019 ), rapeseed (Galanty et al, 2022 ), Chinese cabbage, red cabbage, barley, and wheat (Xiao et al, 2022 ). However, the contents may differ depending on the cultivation method of the plant (Galanty et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%